Estimation of Girth or Diameter Increment from Successive Inventories - Mokashi, V. K.; Acharya, D. P. (Indian Forester, 1967)
The paper deals with the methods of estimation of girth or diameter increment from successive inventories. The basic considerations in employing the ratio of double rising by double effective, in the classical French method of calculating diameter increment by diameter classes from successive inventories, have been examined. Alternathe methods in place of the existing ones or modifications there of have been suggested in the paper. It is felt that the paper would promote interest in the conduct of further research on the subject.